Power of Optical Sensors in Remote Sensing: A Study - Milind Shivaji Kadam; Dr. Kazi Kutubuddin Sayyad Liyakat (International Journal of Satellite Remote Sensing, 2025)
Imagine having eyes that could pierce the veil of the visible, discerning the subtle whispers of light beyond the spectrum our everyday vision allows. This isn't a superpower from science fiction, but the very essence of optical sensors in remote sensing – our planet's watchful, silent sentinels, meticulously translating the electromagnetic symphony into actionable insights. Optical sensors, operating within the visible, near-infrared, and short-wave infrared portions of the electromagnetic spectrum, have revolutionized our ability to observe and understand the Earth from a distance. This abstract explores the fundamental principles and diverse applications of optical sensing in remote sensing. By capturing the unique spectral signatures reflected and emitted by terrestrial features, these sensors provide invaluable data for a wide array of disciplines. From monitoring vegetation health and agricultural productivity to mapping land cover change, detecting water quality, and assessing urban sprawl, optical remote sensing offers a synoptic, repeatable, and often cost-effective means of data acquisition. This work delves into the underlying physics of light-matter interaction, the technological advancements enabling high spatial, spectral, and temporal resolutions, and the crucial role of data processing and analysis in extracting meaningful information. The abstract highlights the continued evolution of optical sensor technology, driven by increasing demands for precision, efficiency, and global coverage, paving the way for more informed environmental management, resource assessment, and scientific discovery.
Keywords: Optical Sensor; Satellite Sensing; electromagnetic radiation; near- infrared (NIR); remote sensing